Pengaruh Ukuran Perusahaan terhadap Tax Avoidance dengan Profitabilitas Sebagai Variabel Moderasi - Wardani, Dewi Kusuma; Wangi, Maria Hermina Vivin (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
The research aims to examine the effect of company size on tax avoidance with profitability as a moderating variable. This study involved manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021 in the basic and chemical industry sub-sectors. The sample was determined purposively, totaling 91 companies. Data collection from www.idx.co.id which is quantitative. The data analysis used is moderation regression analysis. The results of this study include, 1) company size has a positive effect on tax avoidance. 2) profitability strengthens the positive effect of company size on tax avoidance.